Transparansi Digital Sebagai Instrumen Penguatan Akuntabilitas Publik Pada Pemerintah Kota Surabaya Tahun 2020-2024 - Muhammad Hibbani; Agung Firman Sampurna (Universitas 17 Agustus 1945 Samarinda, 2026)
Digital transparency has increasingly been recognized as an important instrument for strengthening public accountability in the era of digital government. However, previous studies have shown that the disclosure of information through digital platforms does not automatically lead to improved accountability. This study aims to analyze how digital transparency functions as an instrument for strengthening public accountability in the Surabaya City Government during the 2020–2024 period. A descriptive qualitative approach was employed using content analysis of seven official digital platforms managed by the Surabaya City Government, including the municipal government portal, the Public Information and Documentation Management Officer (PPID) portal, Open Data Surabaya, the Electronic Procurement Service (LPSE), SP4N-LAPOR!, Suroboyo Hub, and other public information service platforms. The analysis was complemented by a comparison of national Electronic-Based Government System (SPBE) index data and external accountability indicators. The findings reveal that all digital transparency indicators were available and functioned substantively rather than merely fulfilling administrative requirements. Digital transparency contributed to strengthening public accountability through accessible information, disclosure of public documents, integrated information systems, and responsive and traceable complaint-handling mechanisms. Throughout the study period, Surabaya consistently achieved SPBE scores above the national average, reaching 4.49 in 2024. The study also identified five supporting factors: committed leadership, system integration, user orientation, institutional capacity, and effective complaint follow-up mechanisms. These findings suggest that digital transparency can strengthen public accountability when supported by adequate institutional capacity and citizen-oriented information governance.